Circulating exosome-circRNAs mediated downregulation of FGF9 through ceRNA mechanism aggravates renal fibrosis in diabetic nephropathy. - Donglin Yang; Rongjiang Yin; Xiaomin Zhang; Xiaohui Wang; Xiaobin Pei; Zijie Guo; Pengyue Qiao; Kehan Zhu; Lin Wang; Pengchao Du (PLoS ONE)
Diabetic nephropathy (DN) is one of the most serious microvascular complications of diabetes mellitus. It is characterized by progressive tubulointerstitial fibrosis. The aim of this study was to investigate the role of exosomal circular RNA (circRNAs) in regulating fibroblast growth factor 9 (FGF9) expression in DN through a competitive endogenous RNA (ceRNA) mechanism, and to reveal its potential therapeutic targets. Exosomes were isolated from serum of 3 healthy people and 3 patients with DN by ultra-fast centrifugation method, and the circRNA-miRNA-FGF9 regulatory network was constructed by combining high-throughput circRNA sequencing, bioinformatics analysis and weighted co-expression network (WGCNA). The results showed that the expression of circRNAs in serum exosomes of DN patients was significantly down-regulated, and hsa_circ_0006382 and hsa_circ_0019539 targeted the expression of FGF9 by binding to miR-34a-5p, miR-766-3p, miR-147a and miR-27a-3p. Further verification showed that the expression of FGF9 was decreased in renal tissues of DN patients (AUC = 0.902), and its recombinant protein could inhibit the expression of α-SMA and vimentin in high glucose-induced NRK-52E cells, indicating that activation of the circRNA/miRNA-FGF9 network promotes the EMT of renal tubular epithelial cells. This study revealed for the first time the mechanism of the circRNA-miRNA-FGF9 regulatory network in DN fibrosis, providing a theoretical basis for the development of diagnostic markers and targeted therapy strategies based on exosomal circRNA.